2020
DOI: 10.1002/cae.22293
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of psychological virtual simulation experiment teaching system

Abstract: By solving the problem of “invisibility” of human psychological activities through "psychological virtual simulation experimental teaching system" in this paper, the necessity of developing this system, needs analysis, the composition of the overall platform, the design of subsystems, the design of experimental projects, the integration of the system, and the realization methods of various functions of the system were elaborated. This system integrates many courses of psychology specialty, designs several expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Chen, D. et al constructed a virtual simulation experimental teaching system for psychology, which aims to address the level of human mental health and deeply analyze the necessity of the system in the analysis of psychological activities. The use of this system can realize the integration of psychology courses, provide a personalized, immersive experience for different users, and guide the teaching reform of psychology [13]. Bork, F. et al applied augmented reality (VR) technology to the virtual teaching of anatomy, through which students can be helped to better understand the knowledge of anatomy and radiology and fully realize the student-centered learning interaction and enhance students' hands-on integration ability [14].…”
Section: Introductionmentioning
confidence: 99%
“…Chen, D. et al constructed a virtual simulation experimental teaching system for psychology, which aims to address the level of human mental health and deeply analyze the necessity of the system in the analysis of psychological activities. The use of this system can realize the integration of psychology courses, provide a personalized, immersive experience for different users, and guide the teaching reform of psychology [13]. Bork, F. et al applied augmented reality (VR) technology to the virtual teaching of anatomy, through which students can be helped to better understand the knowledge of anatomy and radiology and fully realize the student-centered learning interaction and enhance students' hands-on integration ability [14].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al used the developed virtual platform for teaching and found that it can improve the quality of teaching and promote the effective learning of students 19 . Chen et al established a psychological virtual simulation experiment teaching system according to the user needs of different personnel and found that the system has strong practicability 20 . Tiffany et al studied virtual simulation cases, and the results showed that students improved their understanding ability and interaction ability 21 .…”
Section: Introductionmentioning
confidence: 99%
“…The practical ability of college graduates is closely related to the social-economic level. Strengthening the students' practical ability through various modern information technology and high-quality experimental resources has become widely accepted as technical means in the current academic circle [1,2]. Virtual simulation teaching experiment is the product of the deep integration of virtual reality technology and disciplines and majors.…”
Section: Introductionmentioning
confidence: 99%